Sporenbildung bei Bacillus subtilis: Masse oder Klasse? - Bischofs-Pfeifer, Ilka (Biospektrum, 2020)
Recent timelapse microscopy studies suggest that endospore forming bacteria encounter a quantity-quality tradeoff: Bacillus subtilis can either make more or better spores. Natural isolates employ different life-cycle strategies that are beneficial under different revival conditions. These findings have implications for our understanding of the ecology and evolution of sporulating bacteria and their use in biotechnological applications.
Gesehen am 18.10.2021
Englischsprachige Zusammenfassung vorhanden